MOOEW: Inovasi Hair Tonic Gel Eco-Friendly Berbasis Hydroxyproline Limbah Tulang Ikan Tenggiri dengan Ekstrak Chamomile Solusi Alopesia Kucing - Adela Febry Widiana; Arifianti Arifianti; Sujatmiko Sujatmiko; Maqfira Giri Kusuma Ramadhan; Given Exaudi Girsang (Syntax Corporation Indonesia, 2024)
This research aims to market business potential by implementing sales strategies that produce profitable and sustainable products. MOOEW Hair Tonic has a Return of Investment (ROI) of more than 100% which means that the profits obtained have exceeded the capital. This research uses qualitative exploration methods and economic feasibility studies, resulting in data that this product has a Return of Investment (ROI) of more than 100%, showing significant business sustainability potential. The results show that MOOEW Hair Tonic is able to answer the health care needs of cat fur effectively with a safe material composition and affordable price. This product is expected to encourage concern for the health of pets while supporting environment-based waste reduction. Conclusion, MOOEW Hair Tonic. MOOEW Hair Tonic offers simple, attractive and practical packaging so that it is easy to carry, easy to store and easy to apply. MOOEW Hair Tonic products are sold at affordable prices. However, the product prices we set do not reduce the quality of the raw materials we use.